KONSTRUKSI HUKUM PEMBENTUKAN PERHIMPUNAN PEMILIK DAN PENGHUNI SATUAN RUMAH SUSUN YANG BERKEADILAN - Husnul Khotimah (2023)
Developers must facilitate the formation of The Association of Apartment Unit Residents (PPPSRS) at the latest before the transition period ends. Nevertheless, development actors often still manage flats, causing conflicts between owners and developers. The formulation of the problems raised in this study, how the urgency and legal construction of the establishment of The Association of Apartment Unit Residents (PPPSRS) for apartment buyers after the transition period ends. The research method is normative juridical with approach used is the case approach, approach of legislation (statue approach) and comparative approach. The results of this study indicate that PPPSRS should be established immediately after the transition period ends, in order to create legal certainty in terms of transparency of financial statements and Joint Land Management. The legal construction of PPPSRS is not fair enough for both parties. The interpretation of PPJB as proof of ownership for the formation of PPPSRS is not in line with the interpretation of sale and purchase, Binding Agreement (PPJB) not as proof of ownership when the developer is required to bear the management costs of the unit owner until the issuance of the AJB (deed of sale and purchase). In addition, administrative sanctions against development actors are weak and lack of supervision from the government. Indonesia can adapt the formation of the Joint Management Body (JMB) of Malaysia, which is a combination of developers and unit owners. JMB can stand up to the issuance of legal ownership documents to the owner.